Dopant-free benzothiadiazole bridged hole transport materials for highly stable and efficient perovskite solar cells. (February 2020) - Zhou, Xiang; Kong, Fantai; Sun, Yuan; Huang, Yin; Zhang, Xianxi; Ghadari, Rahim
Abstract: D-A-D typed hole transport materials have been designed and synthesized with benzothiadiazole acceptor unit by introducing electron-withdrawing group fluorine atoms and electron-donating group alkoxy as side group. It is found that the three hole transport materials have a low-lying HOMO energy level and higher hole mobility. Furthermore, when these materials are applied in perovskite solar cell, the higher hole mobility (1.02 × 10 −3 cm 2 V −1 s −1 ) make the B3, which the fluorine atoms on core acceptor without dopants, get a power conversion efficiency of 12.1%, while spiro-OMeTAD based dopant-free perovskite solar cell only shows a 7.96% efficiency. In addition, the long-term stability of the perovskite solar cells based all the three hole transport materials improved greatly, especially B1-based cells show a favorable long-term stability, which keeps a 90% initial efficiency after 10 days at a relative humidity of 30%. Therefore, the D-A-D typed hole transport materials have a good application prospects in the field of perovskite solar cells with the incorporation of appropriate side group. Graphical abstract: Side groups were introduced on core acceptor to develop efficient dopant-free D-A-D HTMs for PSCs. Image 1 Highlights: Three dopant-free D-A-D typed HTMs with benzothiadiazole core were developed. Introducing fluorine or alkoxy in benzothiadiazole will hinder the π-π stacking. Long-term stability of PSCs with D-A-D typed HTMs is enhanced greatly. Increasing electron-withdrawing ability of core may improve hole mobility.